A detailed survey regarding the usage of different ICT technology modes adopted by higher education institutions - Rakshit khajuria; Anuj Sharma; Ashok Sharma (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Information and communication technologies (ICTs) in all aspects of life have become the tools that are present everywhere and in a ubiquitous manner. Over the last twenty to thirty years, it has been noticed that the application of ICT has significantly changed the procedures and courses of almost all the higher education institutions. The higher education field is a highly socially-focused practice and providing quality education is traditionally been linked with the efficient teacher and their capacity for a high level of one-on-one contact with students. The use of ICT in higher education allows for more student-centered learning settings. Due to the reason that the world is quickly developing into a digital place with a huge level of digital information, however, the role of ICT in higher education is becoming increasingly significant and will persistently to grow and evolve in the 21st century. The application of ICT in the teaching and learning process, as well as its effective usage in higher education, depends on a variety of tools and techniques. In this paper, a detailed analysis of various modes adopted by the institutions of higher education is made.